(untitled) (Journal of the College of Languages (JCL), 2020)
The article describes the basic principles of modeling a dictionary article in the “Dictionary of the Language of Russian Folklore Lexicon epics” (M. A. Bobunova, A. T. Khrolenko). Among such principles are the principle of linguocentrism (representation of universal cognitions in strict observance of the traditions of lexicographic science), the principle of anthropocentrism (language learning as a means of human consciousness / subconsciousness), the principle of expansionism (attracting material from various knowledge bases), the principle of explanatory ("explanatory moment"), and fractal principle (synergistic potential of the presented material: nonlinearity and self-similarity; hierarchical organization; irregularity; blurred boundaries, cross-links, or blurred contours, blur; ability to develop, dynamism, etc.). The article also aims to analyze the fine lexicographic structures in the Russian-language dictionary of folklore. As a result, the analysis of the fine lexical structures in the Russian folklore dictionary helped to follow the observance of knowledge-oriented systems and strict adherence to the traditions of lexical science. In addition, the search for new principles for the formulation of the lexicon structures of the Russian language dictionary of the new type of folklore. В статье названы основные принципы моделирования словарной статьи в «Словаре языка русского фольклора: Лексика былины» (М. А. Бобунова, А. Т. Хроленко), среди которых: принцип лингвоцентризма (репрезентация общечеловеческих когниций в строгом соблюдением традиций лексикографической науки); принцип антропоцентризма (изучение языка как средства человеческого сознания / подсознания); принцип экспансионизма (привлечение материала с различных баз знаний); принцип экспланаторности («объяснительный момент»); фрактальный принцип (синергетичечский потенциал представленного материала: нелинейность и самоподобие; иерархическая организация; нерегулярность; нечеткость границ, перекрестные связи, или нечеткость контуров, размытость; способность к развитию, динамичность и т.д.). Статья также направлена на анализ словарных микроструктур в словаре языка русского фольклора. В результате анализ словарных микроструктур в словаре языка русского фольклора помог проследить соблюдение когнитивно-ориентированных установок, и строгом соблюдением традиций лексикографической науки. Кроме того, поиски новых принципов моделирования словарных микроструктур для словаря языка русского фольклора нового типа.